Modification of K-stiffness method for MSE structures on soft ground - N. Tin (2018)
In this paper, a modification of the K-stiffness method, which is used to calculate the reinforcement load of mechanically stabilised earth (MSE) structures on firm foundations, was investigated for application to reinforced structures on soft ground. Current design methods for the estimation of reinforcement loads of reinforced structures on firm foundation, namely the tieback wedge or simplified method, the FHWA structure stiffness method, the original K-stiffness method and the modified K-stiffness method, were applied to calculate the reinforcement loads of two embankments constructed on soft Bangkok clay. From comparisons of the calculated and observed values, a modification of the original K-stiffness method was proposed by suggesting a uniform distribution of the reinforcement loads, and adding one more factor, the settlement factor Φs, to take into account the influence of settlement on the reinforcement loads. © 2011 Thomas Telford Ltd.